2000
DOI: 10.1046/j.1365-2443.2000.00328.x
|View full text |Cite
|
Sign up to set email alerts
|

Schnurri interacts with Mad in a Dpp‐dependent manner

Abstract: Background: Decapentaplegic (Dpp) is a member of the transforming growth factor-b superfamily. Dpp governs various developmental processes in Drosophila through the transcriptional regulation of a variety of genes. Signals of Dpp are transmitted from the cell membrane to the nucleus by Medea and Mad, both belonging to the Smad protein family. Mad was shown to bind to the Dpp-responsive element in genes such as vestigial, labial, and Ultrabithorax. The DNA binding af®nity of Smad proteins is relatively low, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
9

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 65 publications
4
18
0
9
Order By: Relevance
“…3A). However, we, and others, have shown that Drosophila Shn contains at least two additional Smad-interacting domains (Dai et al, 2000;Udagawa et al, 2000), raising the possibility that interactions through other regions contribute to hShn1-Smad complex formation on the Xvent2-BRE. We therefore sought to identify and localize potential Smad-interacting regions within hShn1 by co-expressing hShn1 fragments with hSmad1 and an activated Bmp receptor.…”
Section: Vertebrate Shn Interacts Directly With Smad Proteins and Assmentioning
confidence: 76%
See 1 more Smart Citation
“…3A). However, we, and others, have shown that Drosophila Shn contains at least two additional Smad-interacting domains (Dai et al, 2000;Udagawa et al, 2000), raising the possibility that interactions through other regions contribute to hShn1-Smad complex formation on the Xvent2-BRE. We therefore sought to identify and localize potential Smad-interacting regions within hShn1 by co-expressing hShn1 fragments with hSmad1 and an activated Bmp receptor.…”
Section: Vertebrate Shn Interacts Directly With Smad Proteins and Assmentioning
confidence: 76%
“…Drosophila Schnurri (Shn) is a large DNA-binding transcription factor with multiple, widely separated zinc finger domains, and was one of the first partners identified for Bmp-specific R-Smads (Dai et al, 2000;Udagawa et al, 2000). Shn localizes to the nucleus and interacts with Mad and Med in response to Dpp signaling.…”
Section: Introductionmentioning
confidence: 99%
“…A critical transcription factor mediating this DPP-dependent repression of brinker is the zinc finger DNA-binding protein Schnurri (Shn; German for whiskers; Arora et al, 1995;Grieder et al, 1995;Staehling-Hampton et al, 1995). shn encodes a large protein (ϳ275 kDa) composed of eight zinc fingers (arranged in four clusters), which interacts with Smads (Mad and Medea, orthologs of vertebrate Smads 1/5/8 and 4, respectively) to mediate DPP signaling (Dai et al, 2000;Udagawa et al, 2000). In response to DPP/BMP signaling (Fig.…”
Section: Schnurri a Transcriptional Partner With Multiple Personalitiesmentioning
confidence: 99%
“…An additional stretch of 31 amino acids in XHIVEP1, located between the ZAS-N and isolated zinc fingers (amino acids 703-733), is also weakly conserved between HIVEP1/2 and Drosophila Schnurri proteins. A larger protein fragment of Schnurri that contains this sequence element was shown to form homo-oligomers in vitro [24]. Our data indicate that the HIVEP/Shn protein family has retained remarkable conservation in their overall structure as well as in the sequence of specific domains in different vertebrate species.…”
Section: Discussionmentioning
confidence: 74%
“…The finding that HIVEP members directly interact with members of the Smad family, led us to investigate TGF-b responsive elements for Shn binding sites [21,23,24]. One well characterized TGF-b responsive promoter is that of Xvent-2B [36,37].…”
Section: Dna Binding Specificity Of Xenopus Hivepmentioning
confidence: 99%